Electrical conductivity and structural studies on PVA/CHITOSAN LiCF₃SO₃ solid polymer electrolyte with amino acid as additive / Nor Aisah Ab Razak - Ab Razak, Nor Aisah (2009)
In the present work, PVA and chitosan are used in the based polymer blend. Lithium trifluoromethanesulfonate [LiCF₃SO₃] and amino acid, L-Ieucine have been employed as the doping salt and additive, respectively. The PVA/chtosan solid polymer electrolyte is prepared using solution cast technique. The samples prepared have a plastic-like, free standing consistency, colourless and homogenous. The electrical conductivity of PVA/chitosan blend is in the order of ~10ˉ7 S cm-1) at room temperature. The addition of LiCF₃SO₃ improved the conductivity of PVA/chitosan based electrolyte film to ~10-4 S cm-1. The effect of adding L-Ieucine on the electrical conductivity of the solid polymer electrolyte was investigated. L-Ieucine as a standard amino acid can exist as zwitterions and may provide more complexation sites for interaction between based polymer and doping salt. Slight improvement of ionic conductivity is achieved upon addition of L-leucine. Enhancement in ionic conductivity could be due to increased number of mobile ion and mobility of the ion. Complexation and structural properties of the sample have been investigated by FT- IR, XRD, SEM and DSC. From the fourier transform infrared (FT-IR) spectra, the peak at wave number 1710 cm-1 attributed to C=O has shifted to lower wave number at 1708 cm-1. Result from FT-IR showed that complexation has occurred between salt (LiCF3SO3) and based polymer (PVA /chitosan) or additive (L-leucine). The degree of crystallinity of the polymer electrolytes has been determined through X-ray diffraction (XRD) and indicates the amorphocity structure of the prepared electrolyte samples. The degree of crystallinity of the polymer blend has lowered when complexed with the doping salt. The investigation through the surface morphologies of the samples has been obtained using scanning electron microscope (SEM) which proved the homogeneity for this polymer electrolyte system. For thermal studies using differential scanning calorimetry (DSC) showed lower Tg with highest electrical conductivity for addition of L-Ieucine in complexes polymer electrolytes due to the more flexible local polymer chain and faster in mobility.